Quantifying the performance of a hybrid anion exchanger/adsorbent for phosphorus removal using mass spectrometry coupled with batch kinetic trials. Issue 18 (17th September 2018) - Martin, Benjamin D.; De Kock, Lueta; Gallot, Maxime; Guery, Elodie; Stanowski, Sylvain; MacAdam, Jitka; McAdam, Ewan J.; Parsons, Simon A.; Jefferson, Bruce
ABSTRACT: Increasingly stricter phosphorus discharge limits represent a significant challenge for the wastewater industry. Hybrid media comprising anionic exchange resins with dispersions of hydrated ferric oxide nanoparticles have been shown to selectively remove phosphorus from wastewaters, and display greater capacity and operational capability than both conventional treatment techniques and other ferric-based adsorbent materials. Spectrographic analyses of the internal surfaces of a hybrid media during kinetic experiments show that the adsorption of phosphorus is very rapid, utilising 54% of the total capacity of the media within the first 15 min and 95% within the first 60 min. These analyses demonstrate the importance of intraparticle diffusion on the overall rate in relation to the penetration of phosphorus. Operational capacity is a function of the target effluent phosphorus concentration and for 0.1 mg P L −1, this is, which is 8–13% of the exhaustive capacity. The adsorbed phosphorus can be selectively recovered, offering a potential route to recycle this important nutrient. The main implication of the work is that the ferric nanoparticle adsorbent can provide a highly effective means of achieving a final effluent phosphorus concentration of 0.1 mg P L −1, even when treating sewage effluent at 5 mg P L −1 .